PRODUCTION ENGINEERING CURRICULUM IN INDUSTRY 4.0 IN A BRAZILIAN CONTEXT - Souza, Rodrigo Gris; Quelhas, Osvaldo; Marchisotti, Gustavo; Neto, Julio; Anholon, Rosley; Marinho, C A (The South African Journal of Industrial Engineering, 2020)
Industry 4.0 has been discussed in the scientific community since its inception in 2011. Discussions have focused on characterising what Industry 4.0 is. This industry will increasingly require professionals to perform complex and indirect tasks, such as working together with machines in their daily work. This article aims to analyse the skills and competencies required by Industry 4.0, and to compare them with the scope of production engineering disciplines in six Brazilian universities. As a methodological option, the study is classified as exploratory, bibliographic, and qualitative. It is established that the current syllabus of production engineering courses of Brazilian universities needs to be improved, seeking alignment with the skills and competencies required by Industry 4.0. Although the Industry 4.0 theme is being discussed in the scientific field in Brazilian universities, it is not yet possible to identify any key actions taken to adjust and improve production engineering courses.